Enzyme Engineering
XVIII, 485 p.
Keywords: Enzyme technology continues to maintain a high degree of interest both in the academic and industrial communities. Since the last Enzyme Engineering Conference held in Bad Neuenahr, Federal Republic of Germany, two years ago, an increasing emphasis has been placed on the study and application of immobilized whole cells and organelles. This new emphasis has been reflected in the number of presentations directed to this area. The Fifth International Enzyme Engineering Conference was held in Henniker, New Hampshire, July 29 to August 3, 1979. The organizers of this conference are especially grateful for the generous support received from a number of industrial organizations. The conference was attended by 183 participants representing over 22 countries making this truly an international conference. During this conference, emphasis was placed on a wide variety of areas including: enzyme production, energy transduction, co factor modification, biomass conversion, immobilized enzymes, cells and organelles, and enzymatic synthesis of chemicals and pharma ceuticals. This volume contains most of the presentations and posters presented at the Fifth Conference. The names of the session co chairmen, workshop chairmen, committee members and sponsoring organizations are included as an appreciation of their efforts in making this a successful conference. The preparation of this volume was carried out by the editors including editing and proofing of the individual manuscripts and the final copy of this volume. The editors are indebted to Ms. S.